SST Forced Stratospheric Warming over Southern-Hemisphere High Latitudes - XIA Yan; HU Yongyun (2013)
Satellite observations show significant stratospheric warming trends over Southern-Hemisphere(SH) high latitudes and large portion of the Antarctic polar region in spring season since 1970s.To investigate the relationship between the observed stratospheric warming and sea surface temperature(SST). 中国气象局 1